Urban green spaces, their spatial pattern, and ecosystem service value: The case of Beijing - Xu, Liyan; You, Hong; Li, Dihua; Yu, Kongjian (Habitat international, 2016)
Green spaces provide various kinds of ecosystem service functions. Though some of them, such as the carbon-sinking and biodiversity preservation functions are of value to everyone, others, especially those related to aesthetic and recreational functions, only benefit people who have direct access to green spaces. In urban settings, where ecosystem services in the second category prevail, this means the spatial dimension of urban green spaces, including their richness, accessibility, shape configuration, and distributional characteristics, may considerably influence the realization of their ecosystem service value, and is therefore subject to scrutiny. In this paper, we study how the spatial pattern of urban green spaces influence the realization of their ecosystem service value by utilizing the Hedonic Price Modeling (HPM) method. Taking Beijing as the case, we use the price and other information in the city's developable land transaction records from 2000 to 2004 to construct the HPM, and use Landscape Ecological Metrics (LEM) as proxies of the spatial characteristics of urban green spaces. Four LEMs are used to measure the above mentioned spatial characteristics of urban green spaces. While subject to certain shortcomings in data quality and quantitative estimations of the magnitude of the spatial effects cannot be made, results show that most spatial characteristics of urban green spaces do influence their ecosystem service value as embedded in land value, except for the shape configuration characteristic for which the study yields no result. Further, specifically for Beijing, results indicate that in order to effectively realize their ecosystem service value, green spaces should occupy between 2.20% and 13.40% of the total urban area, located within a 50–550 m range from other developments, with green space patches so divided that each patch occupies more than 3.00% but less than 62.50% of the total green space area, and the ecosystem service value will be at the optimal level when each patch occupies 20.00% of the total green space area. Lastly, we stress the practical significance of the findings, urging an integration of the spatial patterns aspect of urban green spaces in urban planning practices.